The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1182/blood-2011-10-383406
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1/2 study of chemosensitization with the CXCR4 antagonist plerixafor in relapsed or refractory acute myeloid leukemia

Abstract: The interaction of acute myeloid leukemia (AML) blasts with the leukemic microenvironment is postulated to be an important mediator of resistance to chemotherapy and disease relapse. We hypothesized that inhibition of the CXCR4/CXCL12 axis by the small molecule inhibitor, plerixafor, would disrupt the interaction of leukemic blasts with the environment and increase the sensitivity of AML blasts to chemotherapy. In this phase 1/2 study, 52 patients with relapsed or refractory AML were treated with plerixafor in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
311
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(334 citation statements)
references
References 31 publications
19
311
2
1
Order By: Relevance
“…Similar to our observations, Uy et al 21 observed an increase in CXCR4 expression in patients dosed with the CXCR4 inhibitor plerixafor, which is also known to mobilize cells into circulation 22. The apparent increase of surface CXCR4 could be due to an upregulation of CXCR4 or due to the mobilization of a cell population with high levels of surface CXCR4 into the peripheral circulation.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our observations, Uy et al 21 observed an increase in CXCR4 expression in patients dosed with the CXCR4 inhibitor plerixafor, which is also known to mobilize cells into circulation 22. The apparent increase of surface CXCR4 could be due to an upregulation of CXCR4 or due to the mobilization of a cell population with high levels of surface CXCR4 into the peripheral circulation.…”
Section: Discussionsupporting
confidence: 90%
“…Our group and others previously demonstrated that targeting the SDF-1α/CXCR4 axis by CXCR4 inhibition can ameliorate resistance of AML cells to chemotherapy in vitro, in vivo, and in clinical trials (8,9,37). To further explore the mechanism of targeting CXCR4, we evaluated the expression of miRNAs, which have been reported to be differentially expressed and deregulated in pathophysiological conditions such as cancers.…”
Section: Discussionmentioning
confidence: 99%
“…4,36,37,59 In fact, lenalidomide mediated the mobilization of AML cells to PB through downregulation of CXCR4 in non-del5q/5q AML cells but does not affect either the expression or the production of its ligand SDF1 by BM-MSCs. In contrast to plerixafor, lenalidomide does not mobilize normal CD34 + HSPCs to PB.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in contrast to plerixafor, IMiDs do not chemosensitize AML blasts to chemotherapy, further supporting that the addition of IMiDs to cytotoxic chemotherapy seems not feasible in AML. 36,59 Lenalidomide-attenuated pro-inflammatory cytokines including TNFα, γIFN, IL1β and macrophage inhibitory factor (MIF) have been previously described to interact with master pathways/molecules such as CXCR4-SDF1 axis, collagenases, integrins and eicosanoids in controlling cell migration and mobilization. 60-63 Thus, the immunomodulatory effects exerted by IMiDs seem to influence the BM niche in a way non-del5q/5q AML cells physically detach from BM stroma.…”
Section: Discussionmentioning
confidence: 99%